Effectiveness of Land Redistribution Policy In Agrarian Reform Program: Implementation Analysis and Solutions To Land Reform Land Registration Obstacles - Dona Sri Sunardi Wijayanti; Imam Koeswahyono; Letizia Dessy Andreassari (Правові горизонти, 2025)
Presidential Regulation No. 62 of 2023 on the Acceleration of Agrarian Reform Implementation aims to accelerate land redistribution in order to achieve social justice and equitable distribution of land ownership in Indonesia. However, the implementation of this policy still faces various obstacles, especially in land inventory and registration, which are caused by administrative factors, overlapping ownership, and lack of transparency in the land system. This research aims to evaluate the effectiveness of this policy based on Soerjono Soekanto's Legal Effectiveness Theory, which includes legal substance factors, implementing apparatus, supporting facilities, public awareness, and legal culture. The research method used is a normative approach with socio-legal analysis, which examines applicable regulations and their implementation in the field. The results show that although this policy has provided a clear legal basis, its effectiveness is still not optimal due to the lack of coordination between agencies, the low legal literacy of the community regarding agrarian, and bureaucratic constraints in land management. Therefore, it is necessary to improve regulations, digitize the land registration system, strengthen coordination between central and regional governments, and increase legal awareness for land redistribution beneficiaries. With these steps, it is hoped that reformagrarian reform can run more effectively and have a real impact on society.